2005
DOI: 10.1681/asn.2004040339
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Expressed in Tubular Epithelium Plays a Pivotal Role in Renal Fibrogenesis

Abstract: Connective tissue growth factor (CTGF) is one of the candidate factors that are thought to mediate the downstream profibrotic action of TGF-␤. However, its precise role in renal interstitial fibrogenesis has not yet been clarified. It was demonstrated previously that CTGF was expressed in tubular epithelial cells that had been engulfed by interstitial fibrosis in the remnant kidney of the subtotal nephrectomy (SNx) model. In the present study, co-cultures of tubular epithelial cells (mProx24) and tubulointerst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
145
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(158 citation statements)
references
References 37 publications
9
145
0
1
Order By: Relevance
“…13,14 Therapeutic approaches that selectively block endogenous CCN2 activity have proven beneficial effects in fibrotic-related diseases, including experimental lung, liver, vascular, and renal diseases, and some authors have suggested that CCN2 could be a therapeutic target for fibrosis. [12][13][14][15][16] However, cardiac CCN2 overexpression conferred cardioprotection in Angiotensin II-infused mice and in ischemia-reperfusion injury, 17,18 showing that CCN2 exerts protective effects in some pathological settings. These data suggest that before using CCN2 blockers in humans, it is necessary to fully understand the in vivo biological functions of this protein and its fragments.…”
mentioning
confidence: 99%
“…13,14 Therapeutic approaches that selectively block endogenous CCN2 activity have proven beneficial effects in fibrotic-related diseases, including experimental lung, liver, vascular, and renal diseases, and some authors have suggested that CCN2 could be a therapeutic target for fibrosis. [12][13][14][15][16] However, cardiac CCN2 overexpression conferred cardioprotection in Angiotensin II-infused mice and in ischemia-reperfusion injury, 17,18 showing that CCN2 exerts protective effects in some pathological settings. These data suggest that before using CCN2 blockers in humans, it is necessary to fully understand the in vivo biological functions of this protein and its fragments.…”
mentioning
confidence: 99%
“…We previously demonstrated that specific CCN2 mRNA knockdown in tubular epithelial cells significantly attenuated renal fibrosis. 4 These results provide a new insight into the pathologic processes in fibrotic kidney diseases and suggest new targets against which to develop new, selective antifibrotic strategies against a potent profibrotic growth factor, CCN2.…”
Section: Discussionmentioning
confidence: 90%
“…36 We also reported that when a given antisense ODN was injected intravenously into rodents, it was absorbed into the proximal tubular epithelium, where it was retained for nearly 48 h, during which time it could block transcription of a target gene. 3,4,35 Therefore, for groups of male, 5-to 6-wk-old C57BL/6J mice (n ϭ 5, respectively) were purchased from Charles River Laboratories Japan (Yokohama, Japan), and two groups were administered an intravenous injection of the PARP-1 antisense ODN and the others of mutated-antisense ODN (as the negative control) at a concentration of 1.0 mg/kg twice at 48 and 6 h before ureter ligation. At 48 and 96 h after ureter ligation, mice were killed, and obstructed and unobstructed kidney tissues were sampled for RNA extraction, protein extraction, and paraformaldehyde fixation for paraffin blocks.…”
Section: Involvement Of Parp-1 In the Ccn2 Promoter Activity In The Kmentioning
confidence: 99%
See 2 more Smart Citations